Hybridization chain reaction and DNAzyme-based dual signal amplification strategy for sensitive fluorescent sensing of aflatoxin B1 by using the pivot of triplex DNA. (August 2022) - Zou, Li; Zhang, Manjun; Li, Mengyan; Xiao, Zhiyou; Ling, Liansheng
Graphical abstract: Highlights: An aptasensor for AFB1 was developed based on hybridization chain reaction and Zn 2+ -dependent DNAzyme catalyzed cleavage. The proposed fluorescent aptasensor shows high sensitivity for AFB1 detection with a detection limit of 0.22 nmol/L. The detection results of AFB1 in the oil sample show good application prospect in food safety. Abstract: This work developed an enzyme-free fluorescent aptasensor for sensitive aflatoxin B1 (AFB1) detection based on a dual signal amplification strategy of hybridization chain reaction (HCR) and Zn 2+ -dependent DNAzyme. In the presence of AFB1, the aptamer specifically binds to the target, releasing the blocking DNA, which can initiate HCR between hairpin probes H1 and H2. With the addition of the substrate strand (Zn-Sub) and enzyme strand (Zn-Enz) of DNAzyme, HCR product can hybridize with Zn-Sub and Zn-Enz to form triplex DNA and Y-shaped structure together, which further activates the DNAzyme to cleave Zn-Sub. Then, two separated fragments of Zn-Sub respectively hybridize with the fluorescent probe and quencher probe, which results in a dramatic increase in the fluorescence intensity. The proposed aptasensor shows high sensitivity and selectivity for AFB1 detection with a detection limit of 0.22 nmol/L in a linear range of 0.4–16 nmol/L. Moreover, the fluorescent aptasensor exhibits acceptable applicability for detecting AFB1 in oil samples with satisfactory recoveries of 92.2–107.8%. Results are also in agreement with those of the ELISA method, indicating that the fluorescent sensing strategy has great potential applications in food safety control.